2019
DOI: 10.2298/csis180122013l
|View full text |Cite
|
Sign up to set email alerts
|

Improving sentiment analysis for twitter data by handling negation rules in the Serbian language

Abstract: The importance of determining sentiment for short text increases with the rise in the number of comments on social networks. The presence of negation in these texts affects their sentiment, because it has a greater range of action in proportion to the length of the text. In this paper, we examine how the treatment of negation impacts the sentiment of tweets in the Serbian language. The grammatical rules that influence the change of polarity are processed. We performed an analysis of the effect of the negation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…They used datasets in 13 European languages, one of which was Serbian, and three sentiment classes—positive, negative, and neutral—but they found the Serbian data to suffer from quite low inter-annotator agreements. More recently, Ljajić and Marovac [ 39 ] evaluated different ways of handling negation in Serbian, using a corpus of tweets divided into the positive, negative, and neutral class, but they did not discuss what—if any—annotation guidelines they followed and the resulting dataset was not made public.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…They used datasets in 13 European languages, one of which was Serbian, and three sentiment classes—positive, negative, and neutral—but they found the Serbian data to suffer from quite low inter-annotator agreements. More recently, Ljajić and Marovac [ 39 ] evaluated different ways of handling negation in Serbian, using a corpus of tweets divided into the positive, negative, and neutral class, but they did not discuss what—if any—annotation guidelines they followed and the resulting dataset was not made public.…”
Section: Related Workmentioning
confidence: 99%
“…Although rather basic, this method can be useful for languages and domains in which an adequate syntactic parser cannot be found. Since this is the case for the informal register of Serbian, which is predominant in our dataset, and since previous experiments on review-length documents [ 36 ] and tweets in Serbian [ 39 ] showed this approach to be beneficial, we explore its usefulness here, as well. In particular, we experiment with different scopes of negation marking, ranging from a single word after a negation to all the words between a negation and a punctuation symbol.…”
Section: Sentiment Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Labeling the range of negation is of importance in medical records. For the purpose of denoting the negation symbol, a set of negation symbols together with a set of rules proposed in a given paper was used [31].…”
Section: Non-medical Resourcesmentioning
confidence: 99%
“…An overview of the methods for analyzing sentiment data in Twitter is given in [33]. In the paper [34] the authors examined how the treatment of negation impacts the sentiment of tweets in the Serbian language. A study on social influence produced by the contents published on Facebook was presented in paper [35].…”
Section: Related Workmentioning
confidence: 99%